Collaboration as a soft skill in special education teachers - Tsibidaki, Assimina (Revija za elementarno izobraževanje, 2025)
This study explores the role of collaboration as a crucial soft skill for special education teachers (SETs), focusing on its impact on their professional development and teaching practices. Through a qualitative review of 15 studies (2012–2024), findings highlight that, while collaboration enhances inclusive education, challenges persist, including heavy workloads, large class sizes, limited training, and negative attitudes. SETs view collaboration with schools, families, and colleagues as vital to improving both teaching effectiveness and student outcomes. The study underscores the need to integrate collaborative practices into teacher preparation programs to foster professional growth and create more inclusive, supportive learning environments.
Keywords: collaboration; mehke veščine; sistematični pregled literature; sodelovanje; soft skill; special education teachers (SETs); systemic literature review; Učitelji; Vzgoja in izobraževanje oseb s posebnimi potrebami